SET8 localization to chromatin flanking DNA damage is dependent on RNF168 ubiquitin ligase. Issue 1 (2nd January 2020) - Dulev, Stanimir; Lin, Sichun; Liu, Qingquan; Cetintas, Vildan B.; Batada, Nizar N.
ABSTRACT: The DNA damage response (DDR) associated post-translational modifications recruit chromatin remodelers, signaling proteins such as 53BP1 and repair factors to chromatin flanking DNA double strand breaks (DSBs) to promote its repair. Although localization of both RNF168 ubiquitin ligase and SET8 methyltransferase at DSBs is essential for 53BP1's recruitment to DSBs, it is unclear if they do so via the same pathways. Here we report that RNF168 mediates SET8's recruitment to DSBs. Depletion of cellular pool of ubiquitin through proteasome inhibition abolished RNF168 and SET8's localization to DNA damage. Knockdown of RNF8 or RNF168 abolished SET8's recruitment to DNA damage. Moreover, RNF168 and SET8 form stable complexes in vivo . Based on these results we propose a model in which SET8, which despite being a pan-chromatin binding protein, can accumulate several folds at chromatin flanking DSBs through tethering to other proteins that specifically localize to chromatin regions with specific modifications.